Glass Ceiling and Sticky Floor in Agriculture: Male Migration and Culture Effects - Sri Wahyuni; Khairul Hasni; Sylvia Vianty Ranita; Maidalena Maidalena (Indonesian Journal of Innovation Science and Knowledge, 2026)
This study examines the impact of male migration on women’s economic positions within agricultural households, focusing on two gender phenomena: the glass ceiling (upper-income barriers) and the sticky floor (low-income trap). Using a balanced panel dataset of 178 households observed across two time periods (pre- and post-migration), the study employs a Difference-in-Differences framework estimated through a Linear Probability Model with robust standard errors to assess changes in women’s economic status. The estimation results show that households with male migration have a significantly higher likelihood of women breaking the sticky floor and moving toward higher income levels compared to non-migrant households (coefficient = 0.416; p<0.001). However, the interaction between migration status and time period shows no significant evidence of a direct causal effect, suggesting that the observed differences likely reflect pre-existing conditions rather than migration itself. Further analysis reveals that in male-migrant households, the post-migration period positively affects women’s income levels (p<0.05), while adherence to traditional cultural norms negatively influences the likelihood of crossing the glass ceiling and attaining upper-income positions. Qualitative findings reinforce these results: women in male-migrant households experience greater economic roles, particularly in managing remittances and small-scale agricultural enterprises, yet remain constrained by patriarchal decision-making structures that limit their ability to overcome the glass ceiling. Overall, male migration enables women to escape the sticky floor by expanding their participation in agricultural and other rural income-generating activities, but has not fundamentally allowed them to break through the glass ceiling within household power relations